A Layer Stripping Magnetotelluric (MT) 1-D Approach to Identify Sub-surface Resistivity Changes - DENI WARDHANA NIM: 12312041, ANDRY
Magnetotelluric (MT) method resolutions are usually not sufficiently high enough for monitoring small changes of subsurface resistivity. The so-called "layer stripping" approach, which refers to an MT 1-D forward modeling analytical solution, can identify the variations of these small changes. A small resistivity change can be detected on the layer stripping if only on one layer and there is already a previous resistivity measurement data as in the reservoir. It is expected that this method can be used for various types of monitoring reservoirs such as hydrocarbons, gases, geothermal, CCS, etc .. we used used synthetic model with an additional Monte Carlo error as an estimate of results uncertainty. The model refers to the CCS Hontomin CO2 project as a field case. The layer stripping method approach can also be formulated with other type 1-D forward modeling calculations such as matrix mulptiplication, and cotangent hiperbolicus. Previous research indicates that this approach can minimize field data errors that containing noise. Nevertheless both approaches show equivalent results in terms of stability and sensitivity on the apparent resistivity and phase sounding curves. The layer stripping calculation is unstable and has the greatest uncertainty at short periode. This research proposed to contribute an innovative and cost-effective on the monitoring technology with electromagnetic methods. Therefore, the layer stripping approach has great potential although it only can be used with various cautions.